Analisis Pemberdayaan Masyarakat Desa Wisata Candirejo Kecamtan Borobudur Kabupaten Magelang - Adhitya Farhan; Puji Astuti (Journal of Politic and Government Studies, 2018)
Community empowerment in Candirejo Tourism Village is one of the efforts by the village and the government to empower the community through the natural resources and human resources available to manage the tourism potential in Candirejo Village. This has goals to identify the form of community empowerment that has been done in Candirejo village to have an impact on the welfare of the community. The type of research is descriptive analytically through a qualitative approach. Sources of data in this research were obtained from interviews with resource persons and archives or documents relating to research. Sampling technique are using purposive sampling. Data collection techniques that used in this study  are interview, observation, and  documents. This type of research is descriptive analytically through a qualitative approach.Based on the research results can be seen that the tourism potentials in Candirejo tourism village is the potential of nature, the potential of agro tourism, the potential of art and culture, & the potential of home industry. The potential then packaged and managed into a form of community empowerment through a tour package managed by Candirejo Village Cooperative. Potential mapping programs, promotional programs, cooperation programs, and training programs are also underway so that the potential of Candirejo Village is more developed and known. Supporting factors Candirejo village is its potential is still adequate, close to the government, the facilities of the relevant agencies and the participation of the community is classified as active. While the inhibiting factors encountered are still limited funds, limited human resources and weak language in communicating. The existing community empowerment affects the economic and socio-cultural sectors. The impact of the economic sector itself is able to increase the income of the surrounding community and the opening of jobs for the surrounding community in the tourism sector such as local guide, homestay and home industry. The socio-cultural impact of promoting the existing potential and training softskill to the community around to be more developed and able to manage the potential that exists. Keywords: Community Empowerment, Tourism Village, Potential, Cooperation, Impact